Hydrocarbon reserves valuation management - Hussen, Chawarwan M. (Curtin University, 2009)
Given the importance of the reserves disclosures for investors and regulators, it is surprising to them that there has been a lot of focus, which is elaborated on in Chapter 2, on how the reserves data are prepared and reported on by companies. Currently, reserves disclosures in financial statements are not audited by independent public accountants, nor are they audited by any petroleum industry-designated independent evaluators. Performing the critical “reserves evaluator” function currently does not require any recognised certification program or other mandatory industry-wide training requirements.Despite the highly technical nature of the reserves estimation process, both preparers and users of the reserves information know that reserves estimation is not an exact science. Estimates are based on limited data obtained from small regions, which are then extrapolated to the whole field. Reserves estimations are also based on expected production paths over long periods of time. Many alternative procedures are often available and widely used for making similar technical or economic determinations. These factors make reserves disclosures inherently subject to information quality problems. Estimates of proved reserve quantities may often be imprecise and change over time as new information, for example, through new technologies becomes available.Accurate reserves data are extremely important to investors to value and assess the performance of energy companies, and are equally important to regulators and the public given the critical role of the energy sector in the economy. It is clear, then, that reserves data should be disclosed in a way that minimizes the credibility gap that afflicts the current disclosures. Key problem in structuring information about reserves is that relatively objective estimates of reservoir characteristics must be combined with subjective forecasts of project feasibility and commerciality.In this thesis, the Dynamic Reserves Estimation Model (DREM) is considered as a new method to estimate reserves. This model is based on complex parameters; however it has the capability to simplify many problems concerned with reserves estimations.